Is weather related to the number of assaults seen at emergency departments?. Issue 11 (November 2017) - Lemon, D.J.; Partridge, R.
Abstract: Background: It is often suggested that the weather can effect behaviour, increasing the likelihood of assaults and resulting in increased admissions to emergency departments (ED). Therefor a better understanding of the effect of climatic conditions could be useful to help EDs in capacity planning. Whilst other studies have looked at this, none have used data collected specifically to look at ED attendance for assaults or have taken account of potential behaviour modifiers. Methods: We use data from our ED violence surveillance system, the Cardiff Model (CM), married to daily meteorological data to construct negative-binomial regression models. The models are used to estimate changes in the assault rate with changes in temperature, adjusting for day of the week and alcohol consumption. Results: We find that there is 1% increase in the assault rate for every degree increase in the maximum daily temperature (IRR = 1.01, P-value = 0.033). Additionally, different patterns in alcohol consumption at weekends also provide a significant contribution. However, when we generalise this model to represent temperature in terms of factors of standard deviation from the mean temperature, the IRR relationship changes, plateauing at unusually high temperatures (±1.5 SD above the mean). Conclusions: The results presented here suggest that whilst temperature does increase the risk of assaults in Dorset, there may be a limit to its effect. This implies the 'curve-linear' relationship for temperature as suggested by others.